2014
DOI: 10.1245/s10434-014-3857-5
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Prognostic Scores Based on Plasma Fibrinogen and Serum Albumin Levels in Esophageal Cancer Patients Treated with Transthoracic Esophagectomy: Comparison with the Glasgow Prognostic Score

Abstract: Preoperative FA score was significantly associated with postoperative survival in esophageal cancer patients, and the prognostic value is currently being validated in a prospective multicenter cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
69
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 34 publications
8
69
1
Order By: Relevance
“…Although their analysis mainly included patients with adenocarcinomas, and neoadjuvant chemotherapy comprised an epirubicin-based regimen, the study suggests that malnutrition was associated with the lack of response to chemotherapy. Two studies have also reported that low serum Alb is significantly associated with poor prognosis in patients who have undergone esophagectomy for esophageal SCC [23,24]. Although the histological backgrounds were different in these studies, their results are consistent with ours.…”
Section: Discussionsupporting
confidence: 89%
“…Although their analysis mainly included patients with adenocarcinomas, and neoadjuvant chemotherapy comprised an epirubicin-based regimen, the study suggests that malnutrition was associated with the lack of response to chemotherapy. Two studies have also reported that low serum Alb is significantly associated with poor prognosis in patients who have undergone esophagectomy for esophageal SCC [23,24]. Although the histological backgrounds were different in these studies, their results are consistent with ours.…”
Section: Discussionsupporting
confidence: 89%
“…FA score was observed to have an association with tumor invasion depth, lymph node metastasis, and postoperative survival in esophageal cancer patients 15. In our cohort, the FA score showed a statistical relation with smoking status, differential grade, T stage, and TNM stage.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies have demonstrated that decreased albumin levels could not be commonly observed in early or locally advanced esophageal caner patients, leaving it insufficient for risk classification [1315]. Recently, two studies observed better nutrition status in operable esophageal cancer patients than in those with metastatic disease [11, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two studies observed better nutrition status in operable esophageal cancer patients than in those with metastatic disease [11, 15]. Matsuda et al defined the serum albumin cut-off value as 38.0 g/L according to the lower quartile range, and showed that the prognostic indicator based on preoperative plasma fibrinogen and serum albumin levels (FA score) was remarkably predictive of postoperative survival in esophageal cancer patients [15]. Meanwhile, Zhang and his colleagues established the preoperative albumin-globulin score (AGS) based on a cutoff value of 45.6 g/L for albumin, and identified its independent prognostic significance for OS in resectable ESCC [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation